Antifungal plant defensins: increased insight in their mode of action as a basis for their use to combat fungal infections. (April 2017) - Cools, Tanne L; Struyfs, Caroline; Cammue, Bruno PA; Thevissen, Karin
Plant defensins are small, cationic peptides with a highly conserved 3D structure. They have been studied extensively in the past decades. Various biological activities have been attributed to plant defensins, such as anti-insect and antimicrobial activities, but they are also known to affect ion channels and display antitumor activity. This review focuses on the structure, biological activity and antifungal mode of action of some well-characterized plant defensins, with particular attention to their fungal membrane target(s), their induced cell death mechanisms as well as their antibiofilm activity. As plant defensins are, in general, not toxic to human cells, show in vivo efficacy and have low frequencies of resistance occurrence, they are of particular interest in the fight against fungal infections.